Biotransformation of nylon-6, 6 hydrolysate to bacterial cellulose. Issue 19 (21st September 2021) - Zhou, Jiangang; Chen, Yihui; Zhang, Yanbo; Sun, Su; Ullah, Muhammad Wajid; Xu, Weilin
Abstract : In this study, the abundant global textile waste old nylon-6, 6 was utilized as a substrate for bacterial cellulose (BC) production by Taonella mepensis WT-6. Abstract : In this study, the abundant global textile waste old nylon-6, 6 was utilized as a substrate for bacterial cellulose (BC) production by Taonella mepensis WT-6. Briefly, different ratios (dry matter/v, 2.5%, 5%, 10%, or 15%) of nylon-6, 6 waste were treated with 15% sulfuric acid for 2, 4, and 6 h, termed as nylon-6, 6 acid hydrolysate (NAH). The highest depolymerization efficiency of nylon-6, 6 waste was found to be 99.1% at 10% nylon-6, 6 after 4 h of acid hydrolysis and released the maximum hexamethylenediamine (HMD), which resulted in a nearly complete degradation of nylon-6, 6 to HMD, which was then converted to BC by T. mepensis . The structure and properties of BC films produced from Hestrin and Schramm medium (BC-HS) and nylon-6, 6 acid hydrolysate (BC-NAH) media were comparatively studied by Fourier transform infrared spectroscopy (FTIR), mechanical properties, thermogravimetric analysis (TGA), X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), and hydrophilicity analysis. The results demonstrated that the structural features of BC-NAH were comparable to BC-HS, suggesting that nylon-6, 6 waste could be used as an inexpensive substrate for the cost-effective industrial production of BC.